Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.9790/0853-1604055154
|View full text |Cite
|
Sign up to set email alerts
|

Coorelation of Hscrp with Urinary Albumin Creatinine Ratio(UACR) in Patients Of Diabetes with And Without Nephropathy.

Abstract: 5,6,7,8 This study Was undertaken to investigate the role of subclinical inflammation in the pathogenesis of diabetic nephropathy by evaluating the association between the serum High-sensitivity CRP (HS-CRP) (marker of inflammation) and urinary albumin to urinary creatinine ratio. Methods: A prospective case control study of 100 diabetic patients were taken(50 patients with nephropathy and 50 without nephropathy) all these patients hsCRP was compared with UACR(urine albumin to urine creatine ratio).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…The significant and positive correlation between serum hs-CRP levels and severity of albuminuria in our study was in accordance with many other studies in various countries. A research in India about correlation between hs-CRP and urine ACR in diabetic patients with and without DKD showed that the mean hs-CRP level in microalbuminuria group (1.705 mg/L) was significantly lower than in macroalbuminuria group (8.423 mg/L) with p<0.001 (Chauhan et al, 2017). A research in Singapore about CRP and increased albuminuria in a multiethnic Asian population indicated that the prevalence of increased albuminuria increased with increasing CRP category.…”
Section: Discussionmentioning
confidence: 99%
“…The significant and positive correlation between serum hs-CRP levels and severity of albuminuria in our study was in accordance with many other studies in various countries. A research in India about correlation between hs-CRP and urine ACR in diabetic patients with and without DKD showed that the mean hs-CRP level in microalbuminuria group (1.705 mg/L) was significantly lower than in macroalbuminuria group (8.423 mg/L) with p<0.001 (Chauhan et al, 2017). A research in Singapore about CRP and increased albuminuria in a multiethnic Asian population indicated that the prevalence of increased albuminuria increased with increasing CRP category.…”
Section: Discussionmentioning
confidence: 99%